Current approach to the clinical care of adolescents with gender dysphoria - Kyriakou, Andreas; Nicolaides, Nicolas C.; Skordis, Nicos (Acta Biomedica Atenei Parmensis, 2020)
Over the last decade, we have witnessed a significant rise in the number of transgender young people seeking endocrine treatment, of which clinical service and gender dysphoria terminology have attempted to keep pace both in matching demand and better describing the condition. Although helpful guidelines for pubertal suppression and gender affirming hormones have been developed, uncertainties remain regarding treatment and monitoring during treatment, often because the clinical needs of the transgender population have outpaced medical expertise and training. Recently, multidisciplinary team work has evolved due to the increasing complexity of diagnostic and treatment decision-making and has been instrumental in creating a unique service with input from a range of specialists. In this article, the current approach in clinical management of adolescents with gender dysphoria is reviewed, with focus on the endocrine aspect of care in children and adolescents. Questions on what defines optimal clinical care of children and adolescents with gender dysphoria remain and should be the focus of future research.